Justice for Magnitsky: Staging the material document in Elena Gremina's One Hour Eighteen Minutes. (1st September 2018) - Rowson, James
This article investigates the relationship between Russian documentary theatre and the Kremlin's manipulation of justice and the legal system through close analysis of Elena Gremina's One Hour Eighteen Minutes (2010). By tracing the genealogy of documentary theatre in twenty-first-century Russia and framing the play within the context of Vladimir Putin's presidency, this article contends that the act of documentation and the privileging of the document is a vital feature of documentary theatre in Russia. It argues that Gremina's staging of material documents is key to understanding how Russian theatre makers have employed the aesthetics of the 'theatre of the real' to undermine the official discourse of the Putin regime and provoke their audience to consider their own role in challenging these manipulated judicial narratives.